Review and specific of application of DTN netwo - Лукашенко, В. В.; Новгородцев, А. І. (Problems of Informatization and Control, 2015)
Reviewed the features of network architecture DTN. Defined the main differences of the protocols oftraditional networks. Given the directions of application areas and examples of applications